Ferromagnets: Intercalation‐Driven Reversible Control of Magnetism in Bulk Ferromagnets (Adv. Mater. 27/2014). (July 2014) - Dasgupta, Subho; Das, Bijoy; Knapp, Michael; Brand, Richard. A.; Ehrenberg, Helmut; Kruk, Robert; Hahn, Horst
<x xml:space="preserve">Abstract</x> A new concept of controlling magnetism in bulk ferromagnets via reversible lithium chemistry is illustrated. The approach bridges electrochemistry with magnetism and is pertinent to any volume of an intercalation‐friendly ferromagnetic material. An iron oxide (maghemite) nanoparticle ensemble, chosen as a representative system, shows a fully reversible and large variation of saturation magnetization upon a controlled intercalation/de‐intercalation process of Li+ ions. A detailed description of the phenomenon can be found in the article by S. Dasgupta and co‐workers on page 4639. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>